2021
DOI: 10.1684/epd.2021.1299
|View full text |Cite
|
Sign up to set email alerts
|

Early vagus nerve stimulator implantation as a main predictor of positive outcome in pediatric patients with epileptic encephalopathy

Abstract: Objective: We describe a multicenter experience with VNS implantation in pediatric patients with epileptic encephalopathy. Our goal was to assess VNS efficacy and identify potential predictors of favorable outcome. Methods: This was a retrospective study. Inclusion criteria were: ≤18 years at the time of VNS implantation and at least one year of follow‐up. All patients were non‐candidates for excisional procedures. Favorable clinical outcome and effective VNS therapy were defined as seizure reduction >50%. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 73 publications
2
8
0
Order By: Relevance
“…Thus, it is interesting that shorter duration of epilepsy is associated with improved response probability, despite younger patients being less likely responders. This independent effect of duration of epilepsy is also supported by other recent evidence [35,36], but our model is unique in that it looks at the problem as a linear effect rather than through post-hoc subgroup analysis. This growing body of evidence supports earlier intervention with VNS to achieve the best outcomes with the therapy.…”
Section: Age and Duration Of Epilepsysupporting
confidence: 86%
“…Thus, it is interesting that shorter duration of epilepsy is associated with improved response probability, despite younger patients being less likely responders. This independent effect of duration of epilepsy is also supported by other recent evidence [35,36], but our model is unique in that it looks at the problem as a linear effect rather than through post-hoc subgroup analysis. This growing body of evidence supports earlier intervention with VNS to achieve the best outcomes with the therapy.…”
Section: Age and Duration Of Epilepsysupporting
confidence: 86%
“…We did not find any significant difference in age at implantation between the two groups (p ¼ 0.64), but epilepsy duration was significantly shorter in the SR group (p ¼ 0.032). Similar results were published recently by Russo et al 17,18 They studied nearly 90 pediatric patients and reported that the only variable significantly predicting favorable outcomes in children was a shorter time from epilepsy onset to VNS device implantation. 17 Jain and Arya performed a metaanalysis of 101 previous studies and concluded that a shorter duration of epilepsy before VNS implantation was associated with a significantly higher response rate at 1 year.…”
Section: Age At Vns Device Implantation and Epilepsy Durationsupporting
confidence: 86%
“…17 Jain and Arya performed a metaanalysis of 101 previous studies and concluded that a shorter duration of epilepsy before VNS implantation was associated with a significantly higher response rate at 1 year. 19 We agree with their proposal that early referral may be a modifiable factor for desirable seizure outcomes with VNS 19 and early implantation (e.g., within 5 years after seizure onset 17,18 ) may be preferable.…”
Section: Age At Vns Device Implantation and Epilepsy Durationmentioning
confidence: 72%
See 1 more Smart Citation
“…Second, by appropriately identifying drug‐resistance in a patient with epilepsy, the HCP could contemplate and propose other therapeutic options (e.g., epilepsy surgery or ketogenic diet) based on the syndromic diagnosis of the patient in a timely manner. Through the works of many scholars, we know that “early” surgical therapy for drug‐resistant epilepsy is a desired clinical approach and strategy 9,10 . However, we should clarify the meaning of “early” to be pragmatic in practice.…”
Section: Discussionmentioning
confidence: 99%